Penegakan Hukum Panti Asuhan Yang Mengeksploitasi Anak Sebagai Pengemis Melalui Aplikasi TikTok Di Kota Medan - Putri Rachmalia, Amanda; Harisman, Harisman (LPPM Universitas Ekasakti Padang, 2024)
Child exploitation is the act of using children to obtain profits for personal needs without regard to the child's physical and mental condition. This research aims to find out and understand how law enforcement is against perpetrators of child exploitation, especially orphanages as one of the child protection institutions that exploit children as beggars through the TikTok application. The method used in this research is normative juridical. Data collection techniques are carried out by means of library studies and research on literature contained in journals, ebooks, and books. The exploitation of children is regulated in Law Number 35 of 2014, which regulates regulations and sanctions against perpetrators of child exploitation. The exploitation of children can be carried out by anyone, one of these perpetrators is an orphanage. Orphanages are child protection institutions, therefore law enforcement is needed against perpetrators of child exploitation to minimize the exploitation of children.